Disaster Prevention from the Use of Plastic Waste with Ecobrick Project in Buluh Nipis Village - Permatasari, Silvia; Putri, Faradila; Hutagalung, Gracia TM; Rizal, Ibraldi; Innayah, Iffah; Zahara, Nindi; Tusa'diah, Risma; Nasywa, Sabila; Shatilla, Salwa Shabra; Sipahutar, Tegardo Natanael; Andri, Zaki Fadillah (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study aims to investigate the effectiveness of eco-bricks in mitigating plastic waste pollution and to assess the impact of community socialization activities on promoting eco-brick usage in Buluh Nipis Village. It seeks to contribute to sustainable waste management practices and environmental conservation efforts. Method: Utilizing a participatory research approach, the study conducts socialization activities titled